Digital technology, GAFA companies and the changing business world: growth trends in the ethereal economy 20 years later - Sanchez Arnau, Elena; Ferrer Sapena, Antonia; Sánchez Pérez, Enrique Alfonso (Technium Social Sciences Journal, 2023)
Taking a historical perspective, we analyze the economic growth of GAFA companies, and how they fit into the indicators that measure global human development. We explore the limits of growth -assuming that economic growth is inherent to good economic performance- by studying these cases, which are relevant insofar as they lead global economic growth in the new digital-based ("ethereal") economy. Our methodological approach contrasts the growth patterns of GAFA companies with general human growth parameters. This case-to-global study finds clear trends, suggesting that the ethereal economy is constrained only by the limits of human growth.